Managing Sleep and Behavioral Problems in a Preschooler with SATB2-Associated Syndrome. (13th July 2020) - Kumar, Nihit; Zarate, Yuri A.
Abstract : SATB2 -associated syndrome is an autosomal dominant, multisystemic disorder with associated sleep and behavioral abnormalities. Evidence is limited on appropriate management strategies in this population. We describe the medical management of a four-year-old child with poor sleep and significant behavioral problems. After failing initial treatment with melatonin, we initiated treatment clonidine along with high doses of trazodone for sleep. Daytime treatment with quetiapine was added to successfully manage behavioral issues. We present the challenges associated with treatment strategies in children with this syndrome.